Craft horizons (voortgezet als : American Craft (vanaf 1979)) - Webb, Aileen Osborn (New York City : American Crafts Council, 1941)
Craft Horizons is a periodical magazine that documents and exhibits crafts, craft artists, and other facets of the field of American craft. The magazine was founded by Aileen Osborn Webb and published from 1941 to 1979. It included editorials, features, technical information, letters from readers, and photographs of craft artists, their tools, and their works. The magazine both "documented and shaped" the changing history of the American craft movement. It was succeeded by American Craft in 1979. (wikipedia)
Https://www.craftcouncil.org
Online: https://digital.craftcouncil.org/digital/collection/p15785coll2/search
Engels
Tijdschriften
Keywords: toegepaste kunst